A Meta-analysis of Clinical, Patient-Reported Outcomes and Cost of DIEP versus Implant-based Breast Reconstruction. Issue 10 (October 2019) - Khajuria, Ankur; Prokopenko, Max; Greenfield, Max; Smith, Oliver; Pusic, Andrea L.; Mosahebi, Afshin
Abstract : Introduction: Comparative data on clinical outcomes and cost of deep inferior epigastric perforator (DIEP) and implant-based reconstruction (IBR) are limited. We conducted a Preferred Reporting Items for Systematic Review and Meta-analysis-compliant systematic review and meta-analysis to compare clinical, patient-reported outcomes (PROs) and cost. Methods: The protocol was published a priori on PROSPERO (CRD42017072557). EMBASE, MEDLINE, Google Scholar, Cochrane Controlled Register of Trials, Science Citation Index, and ClinicalTrials.gov were searched from January 1994 to August 2018. Two independent reviewers evaluated the articles for inclusion. Study quality was assessed using Grading of Recommendations Assessment, Development, and Evaluation, and risk of bias (RoB) was assessed using Cochrane's RoB in Nonrandomized Studies of Interventions tool. Results: Out of 6, 381 articles screened, 16 were included [unilateral 782 DIEPs, 376 implants; mean age 49 years, follow-up (months): DIEP 29.9; IBR 35.5]. Mean flap loss and fat necrosis rates were 3.97% (SD 4.90) and 9.67% (SD 17.0), respectively. There was no difference in mean length of stay standard mean difference 0.63 [confidence interval (CI) −9.17 to 10.43]; P =0.90. The number of reoperations for complications was significantly lower in DIEP versus IBR [SMD −0.29 (CI −0.48 to −0.09); P < 0.01]. There were no randomized controlled trials. Study quality was low with high RoB. One study reported 11, 941/Quality-adjusted Life Year incremental cost-effectiveness ratio for DIEP, with higher breast Quality-adjusted Life Year (DIEP 19.5; IBR 17.7) using Breast Questionnaire; 3 studies evaluated cost, favoring DIEP. Two comparative studies evaluating PROs favored DIEP. Conclusions: DIEP reconstruction maybe more cost-effective and yield superior PROs. However, poor-quality, bias-ridden studies limit the findings. Adequate reporting of core outcome measures is required to minimize reporting bias and facilitate evidence synthesis. Prospective, multicenter, cohort studies using robust patient-reported outcome measures (PROMs) tools, evaluating cost-effectiveness and contributing to national/international registries, will facilitate national-level policy and shared decision-making.